Semi-Monthly and Turn-of-the-Month Seasonality in Stock Returns : Evidence from Emerging Markets - Mangala, Deepa; Lohia, Vandana (Indian Journal of Finance, 2017)
Behaviour of stock prices has often challenged the established theories and models of financial literature. Monthly effect is also termed as semi-monthly effect and turn-of-the-month effect are among such anomalies which have been documented in stock markets across the world. It refers to the tendency of financial assets to exhibit abnormal returns during the first of the month and at the turn of the month. The objective of the present study was to explore the existence of semi-monthly effect and turn-of-the-year effect in the stock index returns of nine emerging stock markets namely, Argentina, Brazil, China, India, Indonesia, Malaysia, Mexico, Russia, and Taiwan over a time span of more than 17 years commencing from January 1997 through March 2014. The returns of the first half of the month and turn-of-the-month have been compared with the return of second half and rest of the trading month using independent sample t - test, Mann-Whitney U test, and dummy variable regression. The results indicated the presence of semi-monthly effect in four stock markets namely India, Indonesia, Russia, and Taiwan, which exhibited higher mean returns during the first half of the trading month, indicating the presence of semi-monthly effect. The turn-of-the-month represented by sequence of four trading days (-1 to +3) recorded statistically significant positive and higher mean returns than the remaining trading days of the month in the majority of the stock markets investigated.